Surveying the management of Achilles tendon ruptures in the Netherlands: lack of consensus and need for treatment guidelines - Dams, Olivier C. (Knee Surg Sports Traumatol Arthrosc, 2018)
PURPOSE: This study aimed to describe and analyse usual care of Achilles tendon ruptures (ATRs) by orthopaedic surgeons and trauma surgeons in the Netherlands. METHODS: A nationwide online survey of ATR management was sent to all consultant orthopaedic and trauma surgeons in the Netherlands, requesting participation of those involved in ATR management. Data on individual characteristics and the entire ATR management (from diagnosis to rehabilitation) were gathered. Consensus was defined as ≥ 70% agreement on an answer. RESULTS: A total of 91 responses (70 orthopaedic surgeons and 21 trauma surgeons) were analysed. There was consensus on the importance of the physical examination in terms of diagnosis (> 90%) and a lack of consensus on diagnostic imaging (ultrasound/MRI). There was consensus that non-surgical treatment is preferred for sedentary and systemically diseased patients and surgery for patients who are younger and athletic and present with larger tendon gap sizes. There was consensus on most of the non-surgical methods used: initial immobilisation in plaster cast with the foot in equinus position (90%) and its gradual regression (82%) every 2 weeks (85%). Only length of immobilisation lacked consensus. Surgery was generally preferred, but there was a lack of consensus on the entire followed protocol. Orthopaedic and trauma surgeons differed significantly on their surgical (p = 0.001) and suturing techniques (p = 0.002) and methods of postoperative immobilisation (p < 0.001). Orthopaedic surgeons employed open repair and Bunnell sutures more often, whereas trauma surgeons used minimally invasive approaches and bone anchors. Rehabilitation methods and advised time until weight-bearing and return to sport varied. Orthopaedic surgeons advised a significantly longer time until return to sport after both non-surgical treatment (p = 0.001) and surgery (p = 0.002) than trauma surgeons. CONCLUSION: This is the first study to describe the entire ATR management. The results show a lack of consensus and wide variation in management of ATRs in the Netherlands. This study shows that especially the methods of the perioperative and rehabilitation phases were inconclusive and differed between orthopaedic and trauma surgeons. Further research into optimal ATR management regimens is recommended. In addition, to achieve uniformity in management more multidisciplinary collaboration between Dutch and international surgeons treating ATRs is needed. LEVEL OF EVIDENCE: Cross-sectional survey, Level V. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00167-018-5049-5) contains supplementary material, which is available to authorized users.